Clinical Management and Functional Outcomes of Postoperative Achilles Tendon Infections: How Do These Really Do?. Issue 1 (January 2022) - Rider, Carson M.; Hansen, Oliver B.; Drakos, Mark C.
Category: Sports; Other Introduction/Purpose: Achilles tendon repairs and reconstructions have historically been associated with high wound infection rates due to poor vascularity in this region. The risk of postoperative infection, a potentially devastating complication, has led surgeons to pursue non-operative treatment when possible for a range of Achilles tendon pathology. However, new surgical techniques have allowed for smaller incisions and modern, aggressive infection control strategies have limited the morbidity associated with these complications. The present study will review a large case series of Achilles infections, evaluating treatment strategies and outcomes for patients who developed a postoperative infection following treatment for Achilles pathology. Methods: This is a retrospective case series including all patients who experienced a postoperative Achilles tendon infection at a single hospital. Cases from 11 surgeons performed between 2011 and 2020 were reviewed for infection requiring a return to the operating room for irrigation, debridement, and any other necessary interventions. Cases that presented to our institution with an existing infection were also included. Thorough chart review was performed for all patients to determine pathology and initial treatment method, infection management, and clinical outcomes. For patients undergoing Achilles reconstruction with a graft, operative notes were reviewed to determine whether the graft was infected and thus removed during debridement. Clinical follow-up was performed and Patient-Reported Outcomes Measurement Information System (PROMIS) surveys were sent to all patients who were over 1 year out from surgery. Results: 33 patients experienced a postoperative Achilles infection, including 10 who developed infection after surgery at an outside hospital. For patients treated initially at our institution, 8 presented with an acute rupture and 15 with chronic pathology. 12 of 15 chronic cases underwent reconstruction with a graft. For 3 reconstructions and 1 acute repair (12%) the entire Achilles was infected and removed. The graft was partially removed in 2 reconstruction cases (6%) and remained fully intact in the remaining 27 cases (82%). In 2/4 cases in which the Achilles was removed, it ultimately reconstituted as confirmed on MRI. A skin graft or flap was required in 5 of 33 cases (15%) for adequate soft-tissue coverage. In 14 cases (42%), the infection was controlled after a single debridement, 17 cases (52%) required a second debridement, and 2 cases (6%) a third. Postoperative PROMIS scores were available for 17 patients (Table 1). Conclusion: To our knowledge, this case series represents the largest number of postoperative infections analyzed following Achilles tendon surgery. Relatively high postoperative PROMIS scores indicate that infected patients can ultimately reach high levels of physical function with minimal pain when managed appropriately. In many cases the Achilles or graft could be salvaged and in those where it was not, the tendon did at times reconstitute.